KEPUASAN KERJA DAN PERILAKU KEWARGAAN ORGANISASIONAL PADA KARYAWAN - Nicholas Simarmata; Dewi Puri Astiti; I Gusti Ayu Putu Wulan Budisetyani (Universitas Sarjanawiyata Tamansiswa, 2014)
ABSTRACTÂ When employees work, there must be expected by employees. That expectation is the fulfillment of job satisfaction. By the fulfilled of job satisfaction, employees will emerge organizational citizenship behavior. The companies in the beginning need to fulfill employees job satisfaction. But if the job satisfaction of employees is fulfilled, then the companies also feel its benefit, because employees will show organizational citizenship behavior. Therefore, this study will test the relationship between job satisfaction and organizational citizenship behavior on employees.Data collection was conducted at PT. Bali Tourism Development, PO Box 3, 80363 Nusa Dua, Bali in June 2011. The subjects of this study are 50 employees. The reliability score of Job Satisfaction Scale is 0,906 and the reliability score of Organizational Citizenship Behavior scale is 0,965. The normality score of job satisfaction variable is 0.867 and the normality score of Organizational Citizenship Behavior is 0.245. Job satisfaction and organizational citizenship behavioral is linear because its probability score is 0.052. From correlation score is 0,287 and probability score is 0.043, it indicates that there is a relationship between job satisfaction and organizational citizenship behavior. The coefficient of determination is 0.08.From the result of this study is expected to contribute to the sciences such as Industrial Organizational Psychology, Organizational Behavior, Human Resource Management and Industrial Relation and also practically to the sustainability of the company as an employer and employee as workers.Â Keywords: job satisfaction, organizational citizenship behavior, employees